Different Functional and Microstructural Changes Depending on Duration of Mild Cognitive Impairment in Parkinson Disease - Shin, N.-Y.; Shin, Y.S.; Lee, P.H.; Yoon, U.; Han, S.; Kim, D.J.; Lee, S.-K. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: The higher cortical burden of Lewy body and Alzheimer disease–type pathology has been reported to be associated with a faster onset of cognitive impairment of Parkinson disease. So far, there has been a few studies only about the changes of gray matter volume depending on duration of cognitive impairment in Parkinson disease. Therefore, our aim was to evaluate the different patterns of structural and functional changes in Parkinson disease with mild cognitive impairment according to the duration of parkinsonism before mild cognitive impairment.MATERIALS AND METHODS: Fifty-nine patients with Parkinson disease with mild cognitive impairment were classified into 2 groups on the basis of shorter (<1 year, n = 16) and longer (≥1 year, n = 43) durations of parkinsonism before mild cognitive impairment. Fifteen drug-naïve patients with de novo Parkinson disease with intact cognition were included for comparison. Cortical thickness, Tract-Based Spatial Statistics, and seed-based resting-state functional connectivity analyses were performed. Age, sex, years of education, age at onset of parkinsonism, and levodopa-equivalent dose were included as covariates.RESULTS: The group with shorter duration of parkinsonism before mild cognitive impairment showed decreased fractional anisotropy and increased mean and radial diffusivity values in the frontal areas compared with the group with longer duration of parkinsonism before mild cognitive impairment (corrected P < .05). The group with shorter duration of parkinsonism before mild cognitive impairment showed decreased resting-state functional connectivity in the default mode network area when the left or right posterior cingulate was used as a seed, and in the dorsolateral prefrontal areas when the left or right caudate was used as a seed (corrected P < .05). The group with longer duration of parkinsonism before mild cognitive impairment showed decreased resting-state functional connectivity mainly in the medial prefrontal cortex when the left or right posterior cingulate was used as a seed, and in the parieto-occipital areas when the left or right caudate was used as a seed (corrected P < .05). No differences in cortical thickness were found in all group contrasts.CONCLUSIONS: Resting-state functional connectivity and WM alterations might be useful imaging biomarkers for identifying changes in patients with Parkinson disease with mild cognitive impairment according to the duration of parkinsonism before mild cognitive impairment. The functional and microstructural substrates may topographically differ depending on the rate of cognitive decline in these patients.ADAlzheimer diseaseDMNdefault mode networkMCImild cognitive impairmentPCCposterior cingulate cortexPDParkinson diseasePD-ICPD with intact cognitionPD-MCIPD with mild cognitive impairmentPD-MCI-LDPD-MCI with ≥1 year of parkinsonism prior to MCIPD-MCI-SDPD-MCI with <1 year of parkinsonism prior to MCIRSFCresting-state functional connectivity